Enhancement of feline immunodeficiency virus (FIV) infection after DNA vaccination with the FIV envelope. - Richardson, J (1997)
Despite intensive experimentation to develop effective and safe vaccines against the human immunodeficiency viruses and other pathogenic lentiviruses, it remains unclear whether an immune response that does not afford protection may, on the contrary, produce adverse effects. In the present study, the effect of genetic immunization with the env gene was examined in a natural animal model of lentivirus pathogenesis, infection of cats by the feline immunodeficiency virus (FIV). Three groups of seven cats were immunized by intramuscular transfer of plasmid DNAs expressing either the wild-type envelope or two envelopes bearing mutations in the principal immunodominant domain of the transmembrane glycoprotein. Upon homologous challenge, determination of plasma virus load showed that the acute phase of viral infection occurred earlier in the three groups of cats immunized with FIV envelopes than in the control cats. Genetic immunization, however, elicited low or undetectable levels of antibodies directed against envelope glycoproteins. These results suggest that immunization with the FIV env gene may result in enhancement of infection and that mechanisms unrelated to enhancing antibodies underlay the observed acceleration.